Toward the Development of a Program Evaluation Business Model: Promoting the Longevity of Counselling in Schools - Ernst, Kelly; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents a model of comprehensive guidance and counselling integrated within a business context. Counselling services are broadly defined as products, supported or maintained through practices found in human service businesses. Evaluative information can be used as stimuli for stakeholders in developing accountability arguments directed at strengthening counselling services. The article concludes that using program evaluation to position counselling as a business with effective service products may enhance the long-term viability of comprehensive guidance and counselling programs.